PELAKSANAAN TUGAS OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI RIAU TERHADAP LAPORAN PENGADUAN MASYARAKAT KOTA PEKANBARU PADA TAHUN 2017-2019 - Ziadatul Ilmah; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The quality of public services is one of the benchmarks in assessing the success of the bureaucratic reform program implemented by the government. In other words, public service and bureaucratic reform are two things that cannot be separated. In this case, the one with the most authority to assess and supervise this public service is the Ombudsman of the Republic of Indonesia. The Ombusdman is not only at the central level, but there is also an Ombudsman for regional representatives.The background of this research is maladministration problems in the area, especially Pekanbaru Riau, so that the Ombudsman of the Republic of Indonesia Representatives of Riau Province can provide solutions for improving public services whether it is in accordance with the Main Duties of Function (Tupoksi) in Law Number 37 of 2008. This research uses the method descriptive with the type of qualitative research. The scope of the author's research is the implementation of the Ombudsman's duties in receiving reports on suspected maladministration, by using the functions of planning, organizing, mobilizing and supervising reports examining, following up, carrying out investigations. This is an effort to prevent maladministration. The types of data used in this study are primary data with documentation interviews with informants and secondary data obtained from laws and regulations.The results show that the Ombudsman Representative of Riau Province as a public service monitor and has carried out tasks in accordance with the main tasks and functions that have been stipulated in Government Regulation Number 21 of 2011 concerning formation, there are several obstacles, namely a lack of human resources, and a lack of budget. This research is to develop a theory of government management to strengthen the discussion of the implementation of the Ombudsman's duties and can provide input, ideas for Ombudsman representatives in Riau.